(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Crystallins, which represents the major lens protein, play a significant role in ensuring the lens transparency and maintenance of appropriate refractive index of the lens that help in accurate focusing of incident visible light precisely on retina to create clear image perception. Aggregation of lens proteins is known to form the basis of cataract formation. The present study is an attempt to examine the stability of the lens protein aggregates, isolated from human cataract eye lens, against an anionic detergent Sodium dodecyl sulphate (SDS), which is known to disrupt the hydrophobic interaction of protein aggregates. Data that emerged from Congo red (CR), thioflavin T (ThT) and 8-anilino-1-naphthalene sulfonic acid (ANS) binding assaysindicated their amyloidogenic nature. A significant reduction in the bathochromic shift of CR λmax and ThT fluorescence emission intensity were observed after treatment of the aggregated proteins with SDS. In the presence of SDS, a significant change in the number and size of the protein aggregates were observed during their morphological analyses under transmission electron microscopy (TEM). Based on the above data it became evident that the hydrophobic interaction plays a crucial role in formation and stabilizing the protein aggregates during cataract formation.